INVENTORY AND IDENTIFICATION OF SPECIFIC LOCATIONS TECHNOLOGY NEEDS OF AGRICULTURE SUPERIOR COMODITIES IN WEST KALIMANTAN - Rusli Burhansyah (Fakultas Pertanian, Universitas Janabadra, 2017)
Study aims to inventory and identification of specific technology needs and determination of agricultural commodities featured. Assessment was conducted in November until December 2014 conducted in six districts namely been determined intentional production centers: Sambas, Bengkayang, Landak, Pontianak, Kubu Raya, and Pontianak. Assessment method using a survey method. Survey using structured interviews and FGD. Descriptive analysis method used to determine inventory and identification of technology needs. There are 16 leading commodities: seeds, pest and disease control, plant spacing, fertilization, harvest and post-harvest, marketing. Commodities featured: rice, corn, soybean, cassava, aloe, papaya, pineapple, olive, palm, rubber, pepper, coconut, cattle, goats and free-range chicken. Determination of commodities in regions based on legal basis has not been done by the county and city governments. There are several LQ <1: coconut (Kubu Raya), (Pontianak) cattle, (Bengkayang) goats. It requires excellent commodities based on legal basis of local government. Necessary to formulate specifics of location technology needs of agriculture superior commodities.